INNOVATIVE TECHNOLOGIES IN LEARNING THE ENGLISH LANGUAGE - Куценко, Т.І.; Бондаренко, О.І. (Modern engineering and innovative technologies, 2023)
The article highlights the principles of interactive work. The use of information and computer technologies is presented, which opens up new opportunities in teaching, the application of new forms and methods of teaching, and promotes new approaches to th